The role of Gamma Knife radiosurgery in the management of skull base chordoma - Wang, Kuanyu; Gao, Dezhi; Pan, Jian; Bao, Enmeng; Sun, Shibin (Frontiers in Oncology, 2023)
Objective Chordoma is a slow-growing and locally aggressive cancer, which arises from the remnants of the primitive notochord. The first line treatment for the skull base chordoma is neurosurgery. Gamma Knife radiosurgery (GKS) is often be chosen especially in the setting of residual or recurrent chordomas. The purpose of this study is to evaluate the prognosis of patients with skull base chordoma who underwent GKS. Methods The present study was a retrospective analysis of 53 patients with skull base chordomas who underwent GKS. Univariate Cox and Kaplan-Meier survival analysis were performed to analyze the relationship between the tumor control time and the clinical characteristics. Results The 1-, 2-, 3-, and 5-year progression free survival (PFS) rates were 87, 71, 51, and 18%, respectively. After performing the univariate analysis, the clinical characteristics were not found to be significantly associated with the time of PFS; however, surgical history, peripheral dose, and tumor volume did have tendencies to predict the prognosis. Conclusion GKS provided a safe and relatively effective treatment for residual or recurrent chordomas after surgical resection. A higher tumor control rate depends on two approaches, an appropriate dose of radiation for the tumor and the accurate identification of the tumor margins.